View from Nussdorf towards Vienna - Schaffer, Joseph (artist):::Creator::::::::::::; Schaffer, Peter (artist):::Contributor:::::::::::: (bey Artaria Comp; Austria; Vienna)
Color engraving of Nussdorf with Vienna in the distance